(5y+3)(1+y)=0

Simple and best practice solution for (5y+3)(1+y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5y+3)(1+y)=0 equation:


Simplifying
(5y + 3)(1 + y) = 0

Reorder the terms:
(3 + 5y)(1 + y) = 0

Multiply (3 + 5y) * (1 + y)
(3(1 + y) + 5y * (1 + y)) = 0
((1 * 3 + y * 3) + 5y * (1 + y)) = 0
((3 + 3y) + 5y * (1 + y)) = 0
(3 + 3y + (1 * 5y + y * 5y)) = 0
(3 + 3y + (5y + 5y2)) = 0

Combine like terms: 3y + 5y = 8y
(3 + 8y + 5y2) = 0

Solving
3 + 8y + 5y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(1 + y)(3 + 5y) = 0

Subproblem 1

Set the factor '(1 + y)' equal to zero and attempt to solve: Simplifying 1 + y = 0 Solving 1 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + y = 0 + -1 y = 0 + -1 Combine like terms: 0 + -1 = -1 y = -1 Simplifying y = -1

Subproblem 2

Set the factor '(3 + 5y)' equal to zero and attempt to solve: Simplifying 3 + 5y = 0 Solving 3 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5y = 0 + -3 5y = 0 + -3 Combine like terms: 0 + -3 = -3 5y = -3 Divide each side by '5'. y = -0.6 Simplifying y = -0.6

Solution

y = {-1, -0.6}

See similar equations:

| (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= | | 2b+3b-4b+3=17 | | 10y^3-11x^2+2-12y^3-13x^2= | | -82=-2(6-5r) | | 18y^2-18x^3+2-18y^4-18x^5= | | 5(3x+7)-11=54 | | (-8)(-2)= | | 5+4p-8p=-19 | | 14y^3-4x^2+2-6y^3-2x^2= | | x^2+10x+-4=0 | | -9x-8=1x+16 | | 2x=(7x-y) | | 1+2n+6n=-7 | | 7x+96=-5x | | 368317*8= | | 20/x=4/9 | | 415441*9= | | -23=6-5n-4 | | 415441*10= | | 4(x-7)-2=2(x-3) | | 5k-2k=-21 | | 368317*10= | | 10x-8=9x-5 | | 458000*8= | | -16=-3p+p | | 449000*8= | | 3n=4n-4 | | 8n+3n=-22 | | 2x+26=44 |

Equations solver categories